Investigating Students’ Perceptions of the Learning Environment, Use of ICT, Self-Efficacy, and Enjoyment in Primary School Classrooms: Effects and Determinants - Galos, Siobhan Kathleen (Curtin University, 2018)
This study examined primary school students’ perceptions of the learning environment, their use of ICT, and self-reports of self-efficacy, enjoyment of class and enjoyment of ICT use. Findings suggest that students’ learning environment perceptions and their use of ICT have statistically significant impacts on self-efficacy and enjoyment of classes. The results also found important and significant differences for students who are academically at-risk students and those who are not and for male and female students.